Epidermal growth factor receptor (EGFR) overexpression in triple-negative breast cancer: association with clinicopathologic features and prognostic parameters - Atif Ali Hashmi; Samreen Naz; Shumaila Kanwal Hashmi; Muhammad Irfan; Zubaida Fida Hussain; Erum Yousuf Khan; Huda Asif; Naveen Faridi (BMC, 2019)
Abstract Introduction Triple-negative breast cancers are a poor prognostic group of breast cancers that don't respond to conventional hormonal and her2neu targeted therapy. A subset of triple-negative breast cancer is known to overexpress epidermal growth factor receptor (EGFR); however prognostic significance of this biomarker has not been widely studied in our population. Therefore, we aimed to evaluate the frequency of EGFR overexpression in triple-negative breast cancer in our setup and its association with prognostic and predictive factors. Methods We performed EGFR immunohistochemistry on 150 cases of triple-negative breast cancers. Intensity and percentage of EGFR expression were combined to formulate an EGFR score, that was compared with prognostic features of breast cancer and recurrence status of patients. Results Positive EGFR expression was noted in 18.7% ( 28 cases); out of which 16% (24 cases) showed low EGFR expression, whereas high EGFR expression was seen in 2.7% ( 4 cases). No significant association of EGFR expression was noted when compared with various clinicopathological parameters and recurrence status of the patients. Conclusion We found EGFR protein expression in 18.7% of cases while high expression was seen in only 2.7 % cases of triple-negative breast cancer which may harbor underlying genetic alterations like altered EGFR gene copy number, chromosome 7 copy number or average EGFR gene: chromosome 7 ratio; therefore we suggest that molecular tests like FISH to evaluate these EGFR molecular alterations should be performed in EGFR over expressing triple negative breast cancers in our setup to identify patients that can benefit from anti-EGFR targeted therapy. Moreover, regional difference in EGFR expression (high expression in chinese population compared to our population) are may be due to different underlying genetic alterations in triple-negative breast cancers, further necessitating a need of devising personalized therapeutic protocols for locoregional population.